Diabrotica calchaqui, a new species of Luperini (Coleoptera: Chrysomelidae: Galerucinae), from Argentina - Cabrera, Nora Clara (2004)
The new species Diabrotica calchaqui Cabrera Walsh is described and illustrated based on specimens collected from Cachi, Salta Province, Argentina. This new species is assigned to the Diabrotica virgifera group, subtribe Diabroticina, tribe Luperini. D. calchaqui is recognized by the combined characters of elytra green with yellow vittae in some specimens reduced to two or three spots, humeral plicae subparallel, elytral sulcus sometimes obsolete, and internal sac of median lobe with five sclerites. Differences between D. calchaqui with Diabrotica porracea Harold, Diabrotica tumidicornis Erichson, Diabrotica mapiriensis Krysan & Smith, and Diabrotica fulvofasciata Jacoby, of similar morphology, also are discussed. Adults have been found associated with cultivated Cucurbitaceae and wild Asteraceae flowers.